PENGARUH KINERJA CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PERSISTENSI LABA PADA SEKTOR ANEKA INDUSTRI SUB SEKTOR ALAS KAKI, TEKSTIL DAN GARMENT DI INDONESIA - Finy Amelia; Juniarti Juniarti (Business Accounting Review, 2016)
The influence of CSR on the financial performance that are periodically such as ROA, ROE and ROS had been done before. However, research on the influence of CSR to the persistence of earnings that had been made were still very few in previous studies that were Riahi and Belkaoui (2004), Lakshman and Yang (2009), and had never been done in the Indonesian company in the miscellaneous industry sub sector of footwear, textile and garment. The research objectives was to determine whether CSR affected the persistence of earnings in companies engaged in various sectors of industry sub-sectors footwear, textile and garment.This research was conducted on Indonesian various industry companies in the sub sectors of footwear, textile and garment. CSR was measured based on the GRI reporting criteria version 3.1. Meanwhile, earnings persistence measured by using the slope of the earnings per share. This study used several control variables: the operating cycle, sales volatility, volatility of cash flows, and the proportion of negative earnings. The data processing sample of 64 observations used multiple linear regression method with SPSS. The results of the study had not managed to show the significant influence of CSR to earnings persistence. The studies also had not found a significant relationship between the volatility of cash flows, the proportion of negative earnings with earnings persistence. However, the operating cycle and sales volatilitas had significant affect on earnings persistence.